Representation of solutions of one integro-differential operator equation - Linchuk, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We describe solutions of an integro-differential operator equation in the class of linear continuous operators acting in spaces of functions analytic in domains.